Investment Banks, Hedge Funds, and Private Equity - Stowell, David P. (Academic Press, 2017)
As our economy evolves, private equity groups, hedge funds, and investment banks compete and cooperate in different ways.iAiATheir recent innovations are reported and analyzed by the 3rd edition of David Stowell's landmark book, which adds three new cases, significantly revisions of most chapters, and updated figures, tables, and exhibits. It captures the actual work that associates and vice presidents do, providing readers with templates for real transactions. Finally, it provides significantly more content about the ways liquidity is supplied in secondary markets, including an overview of high frequency trading/electronic market making, quantitative trading strategies, and the evolution of cash equities from open outcry pits to fully electronic central limit order books.